Biochemical markers and fertility rate of hydatid cyst isolated from human and animal in Sulaimani province - Hama, Abdulla Ahmed; Ali, Fatimah Mohammed; Mero, Wijdan M S.; hassan, Kalil (Kurdistan Journal of Applied Research, 2017)
Hydatid disease is a helminthic infection, caused by the metacestode stage of cestode belonging to the Echinococcus grnulosus (dog tapeworm). The species and strain identification of Echinococcus are of medical importance for strategic control measuring. The present study achieved to determine and compare fertility and biochemical profiles of hydatid cyst fluid isolated from human, cattle, sheep and goat. The human originated cyst has been found to be more fertile (88%), followed by sheep-originated cyst (85%). The high rate of fertility was found in the liver followed by lungs in all intermediate hosts. However, the statistically significant differences of a biochemical test of cyst fluid among intermediate host were observed just in the uric acid, while the result of biochemical tests Hydatid cyst fluid isolated from liver significantly was higher than that of the lung for the most biochemical tests. The fertility and biochemical parameters value differences directly have related to the location of cyst and strains of E. granulosus. This finding concluded the sheep strain is a predominant strain and responsible for human and animal echinococcosis and sheep is the main intermediate host responsible for the perpetuation of the life cycle of E. granulosus in Sulaimani.